Respuesta :

You have the following function:

f(x) = 4(x + 2)² - 1

In order to find the vertex of the previous function, expand the factor (x + 2)²:

f(x) = 4(x² + 4x + 4) - 1

f(x) = 4x² + 16x + 16 - 1

f(x) = 4x² + 16x + 15

the previous result has the general form:

f(x) = ax² + bx + c

by comparing the previous expression with the result for the given function you have:

a = 4

b = 16

c = 15

the vertex of the function f(x) is given by:

x = -b/2a

by replacing the values of parameters b and a you obtain:

x = -16/2(4)

x = -16/8

x = -2

Next, to find the vertex, it is necessary to calculate f(-2):

f(-2) = 4(-2 + 2)² + 1

f(-2) = 0 + 1

f(-2) = 1

Hence, the vertex is (-2,1)

ACCESS MORE
EDU ACCESS
Universidad de Mexico